A Systematic Review of the Effect of Rotavirus Vaccination on Diarrhea Outcomes Among Children Younger Than 5 Years - Lamberti, Laura M; Ashraf, Sania; Walker, Christa L Fischer; Black, Robert E (The Pediatric infectious disease journal, 2016)
Rotavirus is the leading cause of vaccine-preventable diarrhea among children under 5 globally. Rotavirus vaccination has been shown to prevent severe rotavirus infections with varying efficacy and effectiveness by region. We sought to generate updated region-specific estimates of rotavirus vaccine efficacy and effectiveness. We systematically reviewed published vaccine efficacy and effectiveness studies to assess the region-specific effect of rotavirus vaccination on select diarrheal morbidity and mortality outcomes in children under 5 years of age. We employed meta-analytic methods to generate pooled effect sizes by Millennium Development Goal region. Rotavirus vaccination was both efficacious and effective in preventing rotavirus diarrhea, severe rotavirus diarrhea and rotavirus hospitalizations among children under 5 across all regions represented by the 48 included studies. Efficacy against severe rotavirus diarrhea ranged from 90.6% [95% confidence interval (CI): 82.3-95.0] in the developed region to 88.4% (95% CI: 67.1-95.9) in Eastern/Southeastern Asia, 79.6% (95% CI: 71.3-85.5) in Latin America and the Caribbean, 50.0% (95% CI: 34.4-61.9) in Southern Asia and 46.1% (95% CI: 29.1-59.1) in sub-Saharan Africa. Region-specific effectiveness followed a similar pattern. There was also evidence of vaccine efficacy against severe diarrhea and diarrheal hospitalizations. Our findings confirm the protective efficacy and effectiveness of rotavirus vaccination against rotavirus diarrheal outcomes among children under 5 globally.